Pemberdayaan Masyarakat dalam Produksi Pestisida Organik Ramah Lingkungan - Fitriah Khoirunnisa; Dina Fitriyah; Rita Fitriani (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The use of synthetic pesticides in farming management has had a negative impact on the environment. In general, farmers still use synthetic pesticides, hence not environmentally friendly. Therefore, farming needs to be directed towards environmentally-friendly agricultural activities with the use of organic pesticides. However, the knowledge and skills of farmers in the production of organic pesticides are lacking. The aim of this program is to increase the knowledge and skills of farmer groups in producing organic pesticides. The implementation was applied in the form of training and demonstration of pesticide manufacture. The results of the activity showed that the knowledge and skills of farmers increased, and they were able to produce organic pesticides. The implication is that farmers can produce organic pesticides independently instead of using synthetic pesticides in farm management.